Optical Spectroscopy of X-Mega targets in Carina Nebula : III. The multiple system Tr 16-104 (≡CPD -59° 2603) - Rauw, G. (2001)
We discuss the orbital elements of the multiple system Tr 16-104 which is usually believed to be a member of the open cluster Trumpler 16 in the Carina complex. We show that Tr 16-104 could be a hierarchical triple system consisting of a short-period (2.15 d) eclipsing O7 V+O9.5 V binary bound to a B0.2 IV star. Our preliminary orbital solution of the third body indicates that the B star most probably describes an eccentric orbit with a period of ∼285 or ∼1341 d around the close binary. Folding photometric data from the literature with our new ephemerides, we find that the light curve of the close binary exhibits rather narrow eclipses indicating that the two O stars must be well inside their Roche lobes. Our analysis of the photometric data yields a lower limit on the inclination of the orbit of the close binary of i≥77°. The stellar radii and luminosities of the O7 V and O9.5 V stars are significantly smaller than expected for stars of this spectral type. Our results suggest that Tr 16-104 lies at a distance of the order of 2.5 kpc and support a fainter absolute magnitude for zero-age main-sequence O stars than usually adopted. We find that the dynamical configuration of Tr 16-104 corresponds to a hierarchical system that should remain stable provided that it suffers no strong perturbation. Finally, we also report long-term temporal variations of high-velocity interstellar Ca ii absorptions in the line of sight towards Tr 16-104.